2004
DOI: 10.1177/0002764203261070
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Racism and Affective Responses to Ambiguous Interpersonal Interactions among African American Men

Abstract: The current study examined affective responses to ambiguous interpersonal interactions containing both ambiguous and overtly racist content. Participants included 74 African American males (ages 18-47), half of whom heard a depiction of a negative social interaction with blatantly racist content (BRC). The remaining participants heard a similar scenario containing no racist content (NRC). Negative affect scores were higher for those in the BRC group, yet individuals in the ambiguous (NRC) condition who reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 11 publications
3
53
0
Order By: Relevance
“…Utsey & Payne suggested that other factors, such as coping style, buffer the consequences of racism for some individuals while others are susceptible to its harmful effects. A more recent study by Bennett et al [20] concluded that the perception of racial discrimination may have intense affective consequences for Black men, as participants in their study were expected to ascribe meaning based on prior experiences with racism, cultural beliefs, and expectations.…”
Section: Psychosocial Copingmentioning
confidence: 99%
See 1 more Smart Citation
“…Utsey & Payne suggested that other factors, such as coping style, buffer the consequences of racism for some individuals while others are susceptible to its harmful effects. A more recent study by Bennett et al [20] concluded that the perception of racial discrimination may have intense affective consequences for Black men, as participants in their study were expected to ascribe meaning based on prior experiences with racism, cultural beliefs, and expectations.…”
Section: Psychosocial Copingmentioning
confidence: 99%
“…Psychosocial coping is based on the premise that not necessarily the stressful events, but how the events are managed by an individual influences their mental health. Seven of the studies in this review emphasized the impact that psychosocial coping has on depression in Black men [10,[15][16][17][18][19][20]. While some articles discussed the negative coping strategies used by Black men (e.g.…”
Section: Psychosocial Copingmentioning
confidence: 99%
“…Immediate physiologic responses to perceived racism have been demonstrated in laboratory settings (Clark et al 1999;Harrell et al 2003;Bennett et al 2004;Merritt et al 2006). Although the epidemiologic research on this topic is in its nascence, numerous studies now show that blacks who report experiencing higher levels of race-based discrimination also have higher levels of a range of indicators of psychological distress.…”
Section: Discrimination and Stressmentioning
confidence: 99%
“…Thus, we also examine whether positive affect has incremental effects, above and beyond related personality characteristics (i.e., optimism) in promoting adjustment to perceived racism. Based on findings from previous research (e.g., Bennett, Merritt, Edwards, & Sollers, 2004;Thompson, 1996), we hypothesized that individuals high in perceived racism would report greater levels of psychological distress. We further hypothesized that over and above the effect of optimism, positive affect would incrementally moderate the effect of perceived racism on depressive symptoms.…”
Section: The Present Researchmentioning
confidence: 99%